Pengaruh Pendidikan Kesehatan Menggunakan Media Instagram terhadap Pengetahuan, Motivasi dan Kepatuhan Konsumsi Tablet Tambah Darah pada Siswi - Agustin Yana Safirna; Nino Adib Chifdillah; Bernadetha Bernadetha (Yayasan Literasi Sains Indonesia, 2026)
Anemia remains a common health problem among adolescent girls, partly due to low knowledge, motivation, and adherence to Iron Supplement Tablet consumption. This study aimed to determine the effect of health education delivered through Instagram on knowledge, motivation, and adherence to consumption among female students at SMP Negeri 18 Samarinda. A quantitative one-group pretest-posttest design was employed involving 40 participants selected through proportionate stratified random sampling. Health education was provided via Instagram for seven days. Data were collected using questionnaires and analyzed with the Wilcoxon test. The findings showed significant improvements in knowledge, motivation, and adherence after the intervention. The proportion of respondents with good knowledge increased from 27.5% to 92.5%, strong motivation from 25.5% to 92.5%, and adherence from 27.5% to 82.5%. Statistical analysis indicated significant differences between pretest and posttest scores for all variables (p < 0.05). These results suggest that Instagram-based health education is effective in improving knowledge, motivation, and adherence to consumption among adolescent girls.